Internet consumer versus professional jurisdiction and applicable law - Caamiña Domínguez, Celia M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This article deals with clauses related to jurisdiction and applicable law used by some professionals. By virtue of Article 18 Regulation (EU) 1215/2012, the Terms of Service stablish that the consumer may bring proceedings against the professional in the courts for the place where the consumer is domiciled. According to Article 6 Regulation (CE) 593/2008, there are Terms of Service where the law applicable to the contract is the law of the country where the consumer has his habitual residence, whereas other clauses determine that the law applicable to the contract is the law where the professional has his habitual residence without depriving the consumer of the protection afforded by the law of the country where the consumer has his habitual residence.